2019
DOI: 10.1103/physreve.99.062904
|View full text |Cite
|
Sign up to set email alerts
|

Solitary waves in a granular chain of elastic spheres: Multiple solitary solutions and their stabilities

Abstract: A granular chain of elastic spheres via Hertzian contact incorporates a classical nonlinear force model describing dynamical elastic solitary wave propagation. In this paper, the multiple solitary waves and their dynamic behaviors and stability in such a system are considered. An approximate KdV equation with the standard form is derived under the long-wavelength approximation and small deformation. The closed-form analytical single-and multiple-soliton solutions are obtained. The construction of the multiple-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 77 publications
1
13
2
Order By: Relevance
“…It is indeed not difficult to verify that the derivations of the solutions in Ref. [34] w.r.t the space coordinate x are the same as the bright solitary wave solutions ( 27)- (31). However, we found that the coefficient ij A in the present multiple-solitary wave solutions and those in Ref.…”
Section: ) the Bright Double-solitary Wave Solutionmentioning
confidence: 89%
See 3 more Smart Citations
“…It is indeed not difficult to verify that the derivations of the solutions in Ref. [34] w.r.t the space coordinate x are the same as the bright solitary wave solutions ( 27)- (31). However, we found that the coefficient ij A in the present multiple-solitary wave solutions and those in Ref.…”
Section: ) the Bright Double-solitary Wave Solutionmentioning
confidence: 89%
“…(33) Theoretically, the solitary wave solutions obtained above and the asymptotic solutions constructed in Ref. [34] (see Eqs. ( 30)-( 33) therein) are different representations of the same physical phenomenon.…”
Section: ) the Bright Double-solitary Wave Solutionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, In Reference [14] the approximate bright and dark solitary wave solutions were obtained in the chain of elastic spheres.…”
Section: Introductionmentioning
confidence: 99%